Peningkatan Kemampuan Menulis Teks Pawarta Melalui Motode Pembelajaran Think-Pair-Share Pada Siswa Kelas X Busana Smk Muhammadiyah Kartasura Tahun Pelajaran 2023/2024: Peningkatan Kemampuan Menulis Teks Pawarta Melalui Motode Pembelajaran Think-Pair-Share Pada Siswa Kelas X Busana Smk Muhammadiyah Kartasura Tahun Pelajaran 2023/2024 - Retno Dwi Handayani Retno (LPPM Universitas Widya Dharma, 2023)
Abstract This research aims to improve Javanese Pawarta writing skills through the Think-Pair-Share learning method. This research was carried out at Muhammadiyah Kartasura Vocational School, Sukoharjo, Central Java, Indonesia from September to October 2023 with Javanese Pawarta material. The research methodology used is classroom action research which consists of two cycles. Each cycle consists of four research stages, namely planning, implementation, observation and reflection. The researcher's role as a teaching staff is assisted by an Arts and Culture teacher as a collaborator. The sample chosen in this study consisted of 20 students in class X Clothing for the 2023-2024 academic year using a cluster random sampling technique. The research data was taken through written tests in the form of pre-test and post-test, the research results showed that there was an increase in the average post-test score for Javanese learning outcomes. The average score for students' ability to write news stories in cycle I was 72.25 and completeness. learning reached 65%. The average score for students' ability to write Pawarta in cycle II was 78.15 and learning completion reached 85% and was above the minimum requirement criteria (KKM) value set by the school, namely 75. Thus it can be concluded that the Think- Pair-Share can improve Pawarta's writing skills... : Javanese language; pawarta; learning